Pulmonary perfusion MRI using interleaved variable density sampling and HighlY constrained cartesian reconstruction (HYCR). Issue 3 (24th January 2013) - Wang, Kang; Schiebler, Mark L.; Francois, Christopher J.; Del Rio, A. Munoz; Cornejo, Ma. Daniela; Bell, Laura C.; Korosec, Frank R.; Brittain, Jean H.; Holmes, James H.; Nagle, Scott K.
<x xml:space="preserve">Abstract</x> Purpose: To demonstrate the feasibility of performing single breathhold, noncardiac gated, ultrafast, high spatial‐temporal resolution whole chest MR pulmonary perfusion imaging in humans. Materials and Methods: Eight subjects (five male, three female) were scanned with the proposed method on a 3 Tesla clinical scanner using a 32‐channel phased‐array coil. Seven (88%) were healthy volunteers, and one was a patient volunteer with sarcoidosis. The peak lung enhancement phase for each subject was scored for gravitational effect, peak parenchymal enhancement and severity of artifacts by three cardiothoracic radiologists independently. Results: All studies were successfully performed by MR technologists without any additional training. Mean parenchymal signal was very good, measuring 0.78 ± 0.13 (continuous scale, 0 = "none" → 1 = "excellent"). Mean level of motion artifacts was low, measuring 0.13 ± 0.08 (continuous scale, 0 = "none" → 1 = "severe"). Conclusion: It is feasible to perform single breathhold, noncardiac gated, ultrafast, high spatial‐temporal resolution whole chest MR pulmonary perfusion imaging in humans. J. Magn. Reson. Imaging 2013;38:751–756. © 2013 Wiley Periodicals, Inc.